2019
DOI: 10.31686/ijier.vol7.iss11.1918
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Students With Down Syndrome in Brazilian Schools

Abstract: Down syndrome, or chromosome 21 trisomy, is a genetic change that occurs at the time of conception of a child. People with Down syndrome have intellectual disabilities, this fact contributes to social exclusion, isolation and impairment in their development, since there is much social prejudice regarding this syndrome. Considering the need to include children with Down Syndrome In schools this research aimed to promote a reflection on the process of inclusion of these people in Brazilian schools through the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(17 reference statements)
0
2
0
1
Order By: Relevance
“…It is therefore deemed that they should attend schools or centers meant exclusively for them (Alsheikh, et al, 2019;National Down Syndrome Society, 2023). Families can also oppose the idea of the successful inclusion of students with Down syndrome in regular schools and may thus require support to understand that the inclusion of their children with Down syndrome in regular schools could be a good experience (Alencar et al, 2019;Luiz et al, 2012). People with Down syndrome can benefit from being included in regular schools (Alabri, 2017;Alencar et al, 2019;National Down Syndrome Society, 2023;Sirlopu et al, 2008).…”
Section: Inclusion Of Individuals With Down Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore deemed that they should attend schools or centers meant exclusively for them (Alsheikh, et al, 2019;National Down Syndrome Society, 2023). Families can also oppose the idea of the successful inclusion of students with Down syndrome in regular schools and may thus require support to understand that the inclusion of their children with Down syndrome in regular schools could be a good experience (Alencar et al, 2019;Luiz et al, 2012). People with Down syndrome can benefit from being included in regular schools (Alabri, 2017;Alencar et al, 2019;National Down Syndrome Society, 2023;Sirlopu et al, 2008).…”
Section: Inclusion Of Individuals With Down Syndromementioning
confidence: 99%
“…Families can also oppose the idea of the successful inclusion of students with Down syndrome in regular schools and may thus require support to understand that the inclusion of their children with Down syndrome in regular schools could be a good experience (Alencar et al, 2019;Luiz et al, 2012). People with Down syndrome can benefit from being included in regular schools (Alabri, 2017;Alencar et al, 2019;National Down Syndrome Society, 2023;Sirlopu et al, 2008). It is generally indicated that appropriate education provided to children with Down syndrome in inclusive environments is more beneficial for them than the instruction they receive in exclusive schools or centers (Hughes, 2006).…”
Section: Inclusion Of Individuals With Down Syndromementioning
confidence: 99%
“…Diante disso, é preciso estabelecer estratégias que atendam as práticas inclusivas, de modo que se desenvolva um sistema educacional unificado que seja flexível e que tenha recursos necessários para atender às necessidades dos alunos (ALENCAR et al, 2019a;ARAÚJO;ARAÚJO, 2017). Ainda, sabe-se que o processo de inclusão escolar de um aluno com TOD tem grande complexidade e não se resume a uma receita ou manual, mas é algo construído através de experiências e de vivências ocorridas no espaço escolar (ARAÚJO; ARAÚJO, 2017).…”
Section: Estratégias Inclusivas Ao Aluno Com Transtorno Opositor Desafiadorunclassified